Pitch Estimation in Real Time: Revisiting SWIPE with Causal Windowing - Meier, Peter; Strahl, Sebastian; Schwär, Simon; Müller, Meinard; Balke, Stefan (Proceedings of the International Symposium on Computer Music Multidisciplinary Research (CMMR), 2025)
Pitch estimation in real time is essential for a wide range of Music Information Retrieval (MIR) applications, including intonation monitoring, music education, and interactive systems. Many of these use cases, such as ensemble rehearsal settings, require low-latency, multichannel processing on resource-constrained devices. While recent neural approaches offer high accuracy, they often fall short in real-time performance due to computational demands. In this paper, we revisit the well-established SWIPE algorithm and introduce RT-SWIPE, a real-time variant enabled by using causal windowing. We further propose a delay-tolerant evaluation metric that extends Raw Pitch Accuracy (RPA) to account for algorithmic delays. Experimental results on synthetic signals and multi-track ensemble recordings demonstrate that RT-SWIPE provides a practical balance of latency, accuracy, and efficiency. Although our study focuses on wind orchestra scenarios, the method is broadly applicable to similar real-time setting